Application of The Problem Based Learning Model to Improve Learning Outcomes of Fikih in Zakat Fitrah Materials - Rijal, Asan Saiful; Mukholimah, Siti; Yasin, Mohammad; Mushlihin, Imam Annas; Marwan, Iwan; Fathoni, AB Musyafa'; Sholihuddin, Ahmad (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Looking at several indications that students learning outcomes in the Fiqh subject are still not satisfactory, many students are passive and still afraid to ask the teacher, and students' courage to speak is still lacking, because teachers don't get students used to trying to find answers and ask questions. Regarding these indications, learning models play an important role in the teaching and learning process because the success of learning is influenced by effective models in an institution. This research uses classroom action research methods. In this research, the researcher wants to know how the Problem Based Learning (PBL) model is applied and what the learning outcomes are from applying the PBL model in Class V FIQH learning at MI Darul Falah. The results of this research prove that the application of the PBL learning model can improve student learning outcomes. This can be seen in the first post test of students who scored <75 as many as 6 students (24%) and students who got a score >75 as many as 19 students (76%) with a class average of 84.4. Meanwhile, the second posttest scores of students who got a score <75 were 0 students (0%) and 25 students scored >75 with a class average of 93.2. In cycle II, student learning outcomes increased with a completion percentage of 100%. This is based on the minimum completeness criteria, namely 75 .